ANOMALIES IN MODELLING BUSINESS PROCESS - Suchenia, Anna; Ligęza, Antoni (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
In the field of business process modeling the most popular is the Business Process Modeling Notation (BPMN). BPMN is relevant from a practical point of view while at the same it offers many challenges for software developers and scientists. Specification of a BPMN diagram is relatively precise, but it is only a descriptive form presented at some abstract, graphical level. Most of the work in this area is focused on the use of the possibilities offered by BPMN notation. However, there is still no document analyzing the errors and how to detect and eliminate. The article attempts to analyze issues anomalies that may occur in the BPMN notation. The survey is based on the analysis of literature and own experience of modeling in BPMN. Analyzes allowed us to identify a few of the most common types of anomalies: syntactic anomalies, and structural anomalies.